Large Area Few-Layer Hexagonal Boron Nitride as a Raman Enhancement Material - Nilanjan Basu; Moram Sree Satya Bharathi; Manju Sharma; Kanchan Yadav; Avanish Singh Parmar; Venugopal Rao Soma; Jayeeta Lahiri (Nanomaterials, 2021)
Increasingly, two-dimensional (2D) materials are being investigated for their potential use as surface-enhanced Raman spectroscopy (SERS) active substrates. Hexagonal Boron Nitride (hBN), a layered 2D material analogous to graphene, is mostly used as a passivation layer/dielectric substrate for nanoelectronics application. We have investigated the SERS activity of few-layer hBN film synthesized on copper foil using atmospheric pressure chemical vapor deposition. We have drop casted the probe molecules onto the hBN substrate and measured the enhancement effect due to the substrate using a 532 nm excitation laser. We observed an enhancement of ≈103 for malachite green and ≈104 for methylene blue and rhodamine 6G dyes, respectively. The observed enhancement factors are consistent with the theoretically calculated interaction energies of MB > R6G > MG with a single layer of hBN. We also observed that the enhancement is independent of the film thickness and surface morphology. We demonstrate that the hBN films are highly stable, and even for older hBN films prepared 7 months earlier, we were able to achieve similar enhancements when compared to freshly prepared films. Our detailed results and analyses demonstrate the versatility and durability of hBN films for SERS applications.